2018
DOI: 10.1093/biolre/ioy200
|View full text |Cite
|
Sign up to set email alerts
|

Sources ofall-transretinal oxidation independent of the aldehyde dehydrogenase 1A isozymes exist in the postnatal testis†

Abstract: Despite the essential role of the active metabolite of vitamin A, all-trans retinoic acid (atRA) in spermatogenesis, the enzymes, and cellular populations responsible for its synthesis in the postnatal testis remain largely unknown. The aldehyde dehydrogenase 1A (ALDH1A) family of enzymes residing within Sertoli cells is responsible for the synthesis of atRA, driving the first round of spermatogenesis. Those studies also revealed that the atRA required to drive subsequent rounds of spermatogenesis is possibly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 76 publications
1
26
1
Order By: Relevance
“…RA produced by spermatocytes and Sertoli cells acts redundantly to maintain spermatogenesis ALDH1A generates RA in spermatocytes, but is fully dispensable for spermatogenesis (Beedle et al, 2019;Teletin et al, 2019). Initially, this suggested that ALDH1A-independent sources of RA could compensate for the loss of Aldh1a2 in spermatocytes (Beedle et al, 2019).…”
Section: Function Of Ra During Spermatogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…RA produced by spermatocytes and Sertoli cells acts redundantly to maintain spermatogenesis ALDH1A generates RA in spermatocytes, but is fully dispensable for spermatogenesis (Beedle et al, 2019;Teletin et al, 2019). Initially, this suggested that ALDH1A-independent sources of RA could compensate for the loss of Aldh1a2 in spermatocytes (Beedle et al, 2019).…”
Section: Function Of Ra During Spermatogenesismentioning
confidence: 99%
“…RA produced by spermatocytes and Sertoli cells acts redundantly to maintain spermatogenesis ALDH1A generates RA in spermatocytes, but is fully dispensable for spermatogenesis (Beedle et al, 2019;Teletin et al, 2019). Initially, this suggested that ALDH1A-independent sources of RA could compensate for the loss of Aldh1a2 in spermatocytes (Beedle et al, 2019). However, analysis of compound mutant mice demonstrates that ALDH1A-dependent activities account for all of the RA required for spermatogenesis, and that the Sertoli and spermatocyte sources of RA exert redundant functions in spermatogenesis maintenance (Teletin et al, 2019).…”
Section: Function Of Ra During Spermatogenesismentioning
confidence: 99%
“…In the unperturbed testis, RA from Sertoli cells contributes functionally to both spermatogonial differentiation and meiotic initiation [19]. Recent studies have addressed the question of whether RA produced by pachytene spermatocytes is required for spermatogenesis [19,171,172]. Chemical or genetic depletion of pachytene spermatocytes in adult testes results in delays to both the elongation of the round spermatids and spermiation, but not to spermatogonial differentiation or meiotic initiation [19].…”
Section: Source Of Ra In the Postnatal And Adult Testismentioning
confidence: 99%
“…Conversely, after injection of RA at 4 weeks of age, Sertoli cell-specific Aldh1a1-3-deficient adults displayed abnormalities in spermiation at 24 weeks of age [63], suggesting that RA from Sertoli cells contributes modestly to this process. Moreover, the level of RA required for spermatogonial differentiation is higher than that required for meiotic initiation [171,172], indicating that each transition is sensitive to the local level of RA. Because the postmeiotic transitions are most sensitive following depletion of RA [19], the postmeiotic transitions may require a higher concentration of RA, from both Sertoli cells and pachytene spermatocytes, than the premeiotic transitions.…”
Section: Source Of Ra In the Postnatal And Adult Testismentioning
confidence: 99%
“…Even so, the great redundancy present in the retinoid metabolome, prevents us from establishing a complete list of the enzymes responsible for many important biotransformations of retinoids. Nonetheless, the knowledge of the main embryonic retinoid enzymes provides us with tools to study the roles of endogenous RA by manipulating its levels in tissue-specific manner through conditional gene targeting (Arregi et al, 2016;Beedle et al, 2019;Bonney, Dennison, Wendlandt, & Siegenthaler, 2018;Kumar, Dolle, Ghyselinck, & Duester, 2017).…”
Section: Future Directionsmentioning
confidence: 99%